Circadian Control of Inflammasome Pathways: Implications for Circadian Medicine - Pourcet, Benoit; Duez, Hélène (Frontiers in Immunology, 2020)
The innate immune system senses ‘non-self’ molecules derived from pathogens (PAMPs) as well as endogenous damage-associated molecular patterns (DAMPs) and promotes sterile inflammation that is necessary for injury resolution, tissue repair/regeneration and homeostasis. The NOD-, LRR- and pyrin domain containing protein 3 (NLRP3) is an innate immune signaling complex whose assembly and activation can be triggered by various signals ranging from microbial molecules to ATP or the abnormal accumulation of crystals, thus leading to IL-1β and IL-18 maturation and secretion. Deregulation of the NLRP3 signaling cascade is associated with numerous inflammatory and metabolic diseases including rheumatoid arthritis, gout, atherosclerosis or type 2 diabetes. Interestingly, the circadian clock controls numerous inflammatory processes while clock disruption leads to or exacerbates inflammation. Recently, the biological clock was demonstrated to control NLRP3 expression and activation, thereby controlling IL-1β and IL-18 secretion in diverse tissues and immune cells, particularly macrophages. Circadian oscillations of NLRP3 signaling is lost in models of clock disruption, contributing to the development of peritonitis, hepatitis or colitis. Sterile inflammation is also an important driver of atherosclerosis, and targeting the production of IL-1β has proven to be a promising approach for atherosclerosis management in humans. Interestingly, the extent of injury after fulminant hepatitis or myocardial infarction is time-of-day dependent under the control of the clock, and chronotherapy represents a promising approach for the management of pathologies involving deregulation of NLRP3 signaling.